Finitely curved orbits of complex polynomial vector fields - Mafra,Albetã C. (2007)
This note is about the geometry of holomorphic foliations. Let X be a polynomial vector field with isolated singularities on C². We announce some results regarding two problems: 1. Given a finitely curved orbit L of X, under which conditions is L algebraic? 2. If X has some non-algebraic finitely curved orbit L what is the classification of X? Problem 1 is related to the following question: Let C Ì C² be a holomorphic curve which has finite total Gaussian curvature. IsC contained in an algebraic curve?